Analisis Dilema Kebijakan Pemerintah dalam Menaikkan Harga Subsidi Bahan Bakar Minyak di Indonesia pada Tahun 2022 - Windiarko, Mohammad Adi (Fakultas Ekonomi, Universitas Sanata Dharma Yogyakarta, 2024)
The government officially increased the price of fuel oil as a result of the increase in world oil prices and made the state budget funds swell. This research was conducted with the aim of examining various considerations made by the government when raising fuel prices in Indonesia. This research uses a literature study research method with a qualitative descriptive method. The data sources used are secondary data obtained through journal articles, books, news, and websites. The results of this study found that the government felt a dilemma so that it was forced to increase fuel prices due to the swelling of state budget funds for fuel oil consumption, but on the other hand, the impact if fuel prices increased, the prices of goods and services would increase so that inflation occurred. On the other hand, there is an alternative solution to buy oil from Russia which is below the market price, however, if that happens, it can offend western countries and hurt Indonesia's foreign policy with non-aligned movements. An alternative that the government can take is to increase fuel prices while still providing assistance to ensure that the community does not experience the impact too deeply. In addition the government invite people to switch to using electric vehicles to reduce fuel consumption and reduce the impact of carbon emissions produced, as electric vehicles are considered more economical and environmentally friendly